A review of studies on Badr Shakir Al-Sayyab’s life and poetry - Muhammed, Ghayda Ali; Mohd Noor, Siti Noor Fazelah; Yusoff, Zailin Shah (2020)
This paper is a review of literature of the researches and readings that are related to my study of the celebrated Iraqi poet Badr Shakir Al-Sayyab (1926-1964) and his attitude towards women. Badr Shakir Al-Sayyab is the most studied poet and a lot of studies, books and article in various languages dealt with his life and poetry. Researchers followed various approaches to examine his social status, his political stands and even his psychological condition. However, only a limited number of researches studied his poetry in terms of language and linguistics. Besides, and as far as it is related to our study, researchers did not state whether Al-Sayyab‟s ideological and political stands influence his attitude toward the women.